Pengaruh Motivasi, Kesehatan Kerja, dan Keselamatan Kerja (K3) Terhadap Kinerja Karyawan PT. X di Bumi Serpong Damai - Riptono Riptono; Muhammad As’ad; Mochamad Reza Hafriansyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
This research aim to analyze the effect of Motivation, Occupational Health, and Safety (OHS) on Employee Performance.The amount of population are 70 employee in PT X and 59 people were sampled by Morgan & Krecjie table.Based on research resultsindicates that: Partially show that motivation has a positive and significant influence amounted to 78,9% of employee Performance. In the second Partial results showed that Occupational Health has no positive and significant impact on employee performance by 19%. In the third Partial results showed that Safety has an inverse and significant impact by 60,1% on Employee Performance. The independent variables Motivation, Occupational Health, and Safety are jointly tested by F test proved positive and significant influence on Employee Performance and the magnitude of the effect seen from coefficient of Determination (R2) is 35,4%.